2011
DOI: 10.1039/c1cp21769k
|View full text |Cite
|
Sign up to set email alerts
|

Molecular spectroscopy for ground-state transfer of ultracold RbCs molecules

Abstract: We perform one-and two-photon high resolution spectroscopy on ultracold samples of RbCs Feshbach molecules with the aim to identify a suitable route for efficient ground-state transfer in the quantum-gas regime to produce quantum gases of dipolar RbCs ground-state molecules. One-photon loss spectroscopy allows us to probe deeply bound rovibrational levels of the mixed excited (A 1 Σ + − b 3 Π 0 ) 0 + molecular states. Two-photon dark state spectroscopy connects the initial Feshbach state to the rovibronic grou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
119
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(126 citation statements)
references
References 45 publications
(93 reference statements)
7
119
0
Order By: Relevance
“…In 2008 two groups have reported the formation of ultracold gases of polar LiCs and KRb molecules in ultracold temperatures [7,8]: ultracold LiCs molecules have been obtained by photoassociation of pairs of ultracold Li and Cs atoms and spontaneous decay of excited LiCs * molecule down to the electronic ground state, while ultracold KRb molecules have been created through magnetoassociation of ultracold K and Rb atoms into weakly bound levels of the molecular ground state, followed by stimulated Raman adiabatic passage (STIRAP) toward the lowest rovibrational level [9,10]. There is also a number of other experiments aiming at creating ultracold heteronuclear diatomic alkalimetal molecules in their ground state like RbCs [11,12] and NaK [13], since in contrast with KRb [14] they are stable with respect to the chemical reactions of atom exchange and trimer formation [15].…”
Section: Introductionmentioning
confidence: 99%
“…In 2008 two groups have reported the formation of ultracold gases of polar LiCs and KRb molecules in ultracold temperatures [7,8]: ultracold LiCs molecules have been obtained by photoassociation of pairs of ultracold Li and Cs atoms and spontaneous decay of excited LiCs * molecule down to the electronic ground state, while ultracold KRb molecules have been created through magnetoassociation of ultracold K and Rb atoms into weakly bound levels of the molecular ground state, followed by stimulated Raman adiabatic passage (STIRAP) toward the lowest rovibrational level [9,10]. There is also a number of other experiments aiming at creating ultracold heteronuclear diatomic alkalimetal molecules in their ground state like RbCs [11,12] and NaK [13], since in contrast with KRb [14] they are stable with respect to the chemical reactions of atom exchange and trimer formation [15].…”
Section: Introductionmentioning
confidence: 99%
“…87 Rb 133 Cs molecules have been formed via magnetoassociation in both Innsbruck [28,29] and Durham [30,31]. The Innsbruck group [32] subsequently performed detailed one-and twophoton molecular spectroscopy and, very recently, reported the transfer of molecules to the rovibrational and hyperfine ground state by STIRAP [33].…”
mentioning
confidence: 99%
“…High transfer efficiency requires a high value of Ω 2 =γ for both transitions, where Ω is the Rabi frequency and γ is the natural linewidth. Debatin et al have identified several states suitable for STIRAP [32]. To locate the states, we pulse 20 μW of pump light, polarized parallel to the magnetic field, on the molecules in the jFi state for 750 μs.…”
mentioning
confidence: 99%
“…An attractive alternative is to form ground-state RbCs, which is expected to be collisionally stable because both the exchange reaction 2RbCs → Rb 2 + Cs 2 and trimer formation reactions are endothermic [14]. There has been considerable work on the Feshbach resonances [15] and molecule formation [16,17] in 87 Rb 133 Cs. However, this isotopologue has an interspecies background scattering length that is large and positive, which produces a spatial separation of the dual condensate [18] and enhances losses from three-body collisions [19,20].…”
mentioning
confidence: 99%